Three‐Dimensional Transvaginal Sonography and Magnetic Resonance Imaging for Local Staging of Cervical Cancer: An Agreement Study. (28th March 2016) - Arribas, Sara; Alcázar, Juan Luis; Arraiza, Maria; Benito, Alberto; Minguez, José Angel; Jurado, Matias
Abstract : Objectives: To evaluate the agreement of clinical examination, 2‐dimensional (2D) sonography, and 3‐dimensional (3D) sonography with magnetic resonance imaging (MRI) for local staging of cervical cancer. Methods: We conducted a prospective study including women with a diagnosis of carcinoma of the cervix. All women were staged clinically and underwent 2D and 3D transvaginal sonography and MRI before treatment for assessing tumor size and parametrial, bladder, and rectal involvement using the examiner's subjective impression. Agreement between sonography and MRI was assessed by calculating the κ index and percentage of agreement. Results: Forty women were included (mean age ± SD, 46.6 ± 11.4 years). Eleven had early‐stage (IA and IB1) disease, and 29 had advanced‐stage (IB2–IVB) disease. A significant correlation for tumor size estimation was found between MRI and pelvic examination ( r = 0.754; P < .001), MRI and 2D sonography ( r = 0.649; P < .001), and MRI and 3D sonography ( r = 0.657; P < .001). Agreement for parametrial infiltration between MRI and pelvic examination was fair (κ = 0.26; 95% confidence interval [CI], 0.10–0.54; 62.5% agreement), between MRI and 2D sonography was moderate (κ = 0.41; 95% CI, 0.15–0.66; 70.0% agreement), and between MRI and 3D sonography was good (κ = 0.60; 95% CI, 0.35–0.85; 80.0% agreement). Agreement for bladder involvement between MRI and pelvic examination was moderate (κ = 0.48; 95% CI, 0.10–0.99; 95.0% agreement), between MRI and 2D sonography was moderate (κ = 0.48; 95% CI, 0.10–0.99; 95.0% agreement), and between MRI and 3D sonography was very good (κ = 0.84; 95% CI, 0.55–1.0; 97.5% agreement). Agreement for rectal involvement was not calculated because of the very small number of cases. Conclusions: Three‐dimensional sonography showed good agreement with MRI for assessing parametrial infiltration and bladder involvement in cervical cancer.